Du processus de Barcelone à l’Union pour la Méditerranée : regards croisés sur les relations euro-maghrébines - Aomar Baghzouz (L’Année du Maghreb)
Are relations between Europe and the countries of the Maghreb in perpetual crisis ? One is tempted to say yes in view of the differences and misunderstandings that dog the process, from the Barcelona Process to the Union for the Mediterranean. If Europeans do not come from Mars or Maghrebins from Venus, to borrow Robert Kagan’s famous metaphor, their respective approaches, as well as the purposes and outcomes of trans-Mediterranean cooperation are often discordant, even if they have been formalized as “cooperation agreements”. By focusing on perceptual differences, this study attempts to present comparative views on Euro-Maghrebin relations (EMP, ENP, UM) in evaluating the opportunity for greater convergence between the two shores.